Towards an Ecclesial Synodality - Luciani, Rafael (Asian Horizons, 2025)
This article explores the theological and ecclesiological foundations of synodality as the defining paradigm for the Church in the third millennium. Drawing from the Second Vatican Council, particularly Lumen Gentium, it situates the Church’s identity in the People of God as the central hermeneutical criterion, over and above hierarchical structuring. The recovery of this conciliar vision emphasizes baptismal dignity, co-responsibility, and mutual reciprocity among all the faithful—christifideles. The article examines how synodality matures the ecclesiology of the People of God by reconfiguring ecclesial life through practices of reciprocal listening, communal discernment, and cultural integration, fruit of the theology of the sensus fidei of all the People of God. It further reframes episcopal collegiality within a broader ecclesial synodality that recognizes the active subjectivity of all the baptized. The emergence of new synodal institutions in Latin America, such as the first Ecclesial Assembly and the Ecclesial Conference of the Amazonia, exemplifies this transition towards an ecclesial synodality. Therefore, synodality is calling for renewed mentalities and relationships, communicative dynamics, and institutional reforms proper to a constitutively synodal Church in mission.